Firm Capabilities and Growth Strategies: The Moderating Role of Institutional Factors (2020)
Building on Resource-Based View (RBV) and Institutional Theory (IT), we decided to study the internal and external factors that affect the choice between different growth strategies in small and medium enterprises (SMEs) in an emerging economy. We started identifying that there is a direct relationship between technological resources and an organic growth strategy, financial resources and an acquisitive growth strategy, and networking capabilities and a hybrid growth strategy. We argue that the intensity of these relations is moderated by institutional factors, such as a country’s intellectual property protections (for organic strategies), credit access (for acquisitive strategies), and trust in the business environment (for hybrid strategies). We based our findings on 450 face-to-face surveys with CEOs from firms in the Electronic Technology, Information, and Communication Sector (ETICS) in Mexico. Managerial implications are also discussed in the paper, as well as future avenues of research.Building on Resource-Based View (RBV) and Institutional Theory (IT), we decided to study the internal and external factors that affect the choice between different growth strategies in small and medium enterprises (SMEs) in an emerging economy. We started identifying that there is a direct relationship between technological resources and an organic growth strategy, financial resources and an acquisitive growth strategy, and networking capabilities and a hybrid growth strategy. We argue that the intensity of these relations is moderated by institutional factors, such as a country’s intellectual property protections (for organic strategies), credit access (for acquisitive strategies), and trust in the business environment (for hybrid strategies). We based our findings on 450 face-to-face surveys with CEOs from firms in the Electronic Technology, Information, and Communication Sector (ETICS) in Mexico. Managerial implications are also discussed in the paper, as well as future avenues of research.